2016
DOI: 10.1096/fj.201600204r
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Notch rescues the angiogenic potential impaired by cardiovascular risk factors in epicardial adipose stem cells

Abstract: The epicardial adipose tissue (EAT) is a reservoir of adipose-derived stem cells (ASCs), with as yet unknown effects on myocardial and coronary arteries homeostasis. The purpose of this study was to investigate the angiogenic function of epicardial ASCs and their regulation by the common cardiovascular risk factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…To understand the functional effect of differences in transcriptional expression between MSCs originating from IP and NU tissue, a matrigel-based angiotube formation assay that reflects the early stages of angiogenesis was performed [ 51 , 52 ], using conditioned IP- and NU-MSC growth media. Some angiogenesis was observed using unconditioned MSC growth media; therefore, this was used as a baseline and the contribution of MSC conditioning was standardised against this.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the functional effect of differences in transcriptional expression between MSCs originating from IP and NU tissue, a matrigel-based angiotube formation assay that reflects the early stages of angiogenesis was performed [ 51 , 52 ], using conditioned IP- and NU-MSC growth media. Some angiogenesis was observed using unconditioned MSC growth media; therefore, this was used as a baseline and the contribution of MSC conditioning was standardised against this.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs originating from IP and NU tissue were seeded in cell culture flasks (Corning Inc., New York, NY, USA) and incubated under standard conditions in MSC growth media (StemMACS Media). At 80% confluence, supernatant was removed and new MSC growth media was added, as previously described [51]. Following a further 72 h incubation, MSC conditioned media was centrifuged at 300× g for 10 min to eliminate dead cells and debris, and the supernatant was then frozen at −80 • C until use.…”
Section: In Vitro Angiogenesismentioning
confidence: 99%
“…Few studies have analyzed the presence and function of heart adipose tissue-derived stem cells, neither in animal [45, 46] nor in human [19] models, and in none of them, their angiogenic potential has been analyzed and compared. Previous studies in our group have shown how ASCs derived from the subcutaneous adipose tissue, independently of the BMI, have no ability to form tubes in a Matrigel-based experiment [11], but here, we demonstrate for the first time that both mASCs and pASCs, when seeded in a 3D Matrigel surface and cultured with EGM-2 medium, are able to form capillary-like ring structures, independently of cardiac fat location and of atherosclerosis severity in the LAD indicating a proangiogenic function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have described that ASCs, in both humans and in rats, are functionally affected by cardiovascular risk factors (CVRFs) [ 22 , 27 , 28 ]. Particularly epicardial ASCs in animals with CVRFs lose their original angiogenic potential [ 29 ] or SAT-ASCs are committed to the adipogenic lineage, while their proliferation rate and proangiogenic potential are impaired in patients with obesity [ 22 , 30 ].…”
Section: Introductionmentioning
confidence: 99%